2018
DOI: 10.1111/cas.13855
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid reverses epithelial‐mesenchymal transition in paclitaxel‐resistant cells by inhibiting nuclear factor kappa B and upregulating gap junctions

Abstract: Paclitaxel is a widely used chemotherapy drug, but development of resistance leads to treatment failure. Tumor cells that are treated with a sublethal dose of paclitaxel for a long period of time show the epithelial‐mesenchymal transition (EMT) phenotype, which leads to metastasis and resistance. All‐trans retinoic acid (ATRA) is always used in combination with paclitaxel and can reverse EMT in many types of cancer cells. The ability of ATRA to reverse EMT in chemoresistant cells is still unknown. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…For example, for over 10 years, ATRA was used in combination with paclitaxel to overcome the paclitaxel-resistance after long-term chemotherapy that establishes a phenotype with higher metastatic ability. Only recently it was showed that ATRA reverse the epithelial-mesenchymal transition associated with paclitaxel resistance inhibiting NFkB, and up-regulating the gap junctions [268].…”
Section: Tumor Progression: Cscs and Invasionmentioning
confidence: 99%
“…For example, for over 10 years, ATRA was used in combination with paclitaxel to overcome the paclitaxel-resistance after long-term chemotherapy that establishes a phenotype with higher metastatic ability. Only recently it was showed that ATRA reverse the epithelial-mesenchymal transition associated with paclitaxel resistance inhibiting NFkB, and up-regulating the gap junctions [268].…”
Section: Tumor Progression: Cscs and Invasionmentioning
confidence: 99%
“…The PI3K-Akt pathway plays a key role in the regulation of apoptosis by NF-κB (36). NF-κB activation results in resistance to many chemotherapeutic drugs, whereas its suppression is known to provide effective therapeutic benefits in chemotherapy treatments (20,21). We found that resveratrol and cetuximab both inhibit NF-κB in these cells, and cells treated with the combination of these two agents have the lowest NF-κB level in their nuclei.…”
Section: Discussionmentioning
confidence: 80%
“…Western blotting was carried out as previously described (21). Briefly, protein samples were suspended in an SDS loading buffer.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In CRC cell lines treatment with ATRA led to decreased proliferation, sphere formation and aldehyde dehydrogenase (ALDH) + CSC-population size by inducing neuroendocrine differentiation [ 29 ]. Moreover, Shi and colleagues found evidence that ATRA reverses EMT in chemotherapy resistant CRC cell lines [ 31 ]. Furthermore, a study with NMYC -amplified neuroblastoma cells could show that a combined treatment of ATRA and a peptide derived from tenascin-C induced differentiation and led to a decrease of NMYC protein [ 27 ], highlighting the involvement of ATRA in NMYC signaling.…”
Section: Introductionmentioning
confidence: 99%